2022
DOI: 10.1039/d2qi01109c
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the dynamics of a mitochondrial microenvironment during apoptosis under two-photon fluorescence lifetime microscopy using a cyclic iridium(iii) complex

Abstract: Mitochondria-mediated apoptosis is a major mode of cell death and is inextricably linked to various pathological processes such as tumorigenesis. However, there is still a paucity of non-toxic tools that...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Tian and co-workers have developed an iridium(III) complex bearing a long and flexible alkyl chain (667) that can monitor apoptosis by tracking mitochondrial viscosity. 1251 Additionally, the complex has been used to examine the differences in the microenvironment of tumor and normal tissues in a mouse model, revealing a higher viscosity level in the tumor microenvironment. Zhang, Zhang, and co-workers have developed two mitochondria-targeting viscosity-responsive iridium(III) complexes ( 668) for PDT applications.…”
Section: Viscositymentioning
confidence: 99%
See 1 more Smart Citation
“…Tian and co-workers have developed an iridium(III) complex bearing a long and flexible alkyl chain (667) that can monitor apoptosis by tracking mitochondrial viscosity. 1251 Additionally, the complex has been used to examine the differences in the microenvironment of tumor and normal tissues in a mouse model, revealing a higher viscosity level in the tumor microenvironment. Zhang, Zhang, and co-workers have developed two mitochondria-targeting viscosity-responsive iridium(III) complexes ( 668) for PDT applications.…”
Section: Viscositymentioning
confidence: 99%
“…On the basis of its viscosity-sensitive emission lifetime and large TPA cross-section ( δ 750nm = 444 GM), complex 666f has been utilized for real-time monitoring and quantitative measurements of changes in mitochondrial viscosity using TP-PLIM, which shows that dysfunctional mitochondria experience a significant but heterogeneous increase in viscosity (Figure ). Tian and co-workers have developed an iridium(III) complex bearing a long and flexible alkyl chain ( 667 ) that can monitor apoptosis by tracking mitochondrial viscosity . Additionally, the complex has been used to examine the differences in the microenvironment of tumor and normal tissues in a mouse model, revealing a higher viscosity level in the tumor microenvironment.…”
Section: Luminescent Transition Metal Complexes As Probes For Microen...mentioning
confidence: 99%
“…As fluorescence lifetime is an intrinsic property of fluorescence probes, FLIM is not influenced by concentration variations, which can be affected by cell volume changes or photobleaching . Additionally, the sensitivity of fluorescence lifetime to microenvironments enables the visualization and quantification of biophysical parameters such as polarity and viscosity within cells. Thus, two-photon FLIM (TP-FLIM) is a valuable tool for measuring changes or differences of microenvironments in subcellular regions or in vivo . To our knowledge, although a few studies have reported the correlation between the polarity change of LDs and the fluorescence lifetime by using one-photon FLIM, , no research has yet reported the polarity differences of LDs in vitro and in vivo by using TP-FLIM. In this study, TBPCPP, a polarity-sensitive two-photon fluorescence lifetime probe for LDs with a donor (D)-acceptor (A)-π-acceptor (A) structure was designed and synthesized by using a facile method (Scheme ).…”
Section: Introductionmentioning
confidence: 99%